Lung exposure during simultaneous myocardial revascularization and lung surgery through median sternotomy - Jagielak, Dariusz; Kozaryn, Radoslaw; Pawlaczyk, Rafal; Siondalski, Piotr; Rzyman, Witold; Rogowski, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Coronary artery disease is a frequent comorbidity in patients undergoing major thoracic surgery. Simultaneous operations eliminate the necessity of a second operation and, more importantly, minimize the delay in compulsory postoperative oncological therapy. We describe a relaxing incision in the contralateral pericardium, which allows for simple displacement of the heart. This maneuver improves exposure of the pulmonary hilum and middle mediastinum on the side of resection.